ANALISIS PENERAPAN SISTEM DAN PROSEDUR PENGADAAN PERSEDIAAN OBAT DI PUSKESMAS MATAKALI KABUPATEN POLEWALI MANDAR - Bertha Beloan; Krisdayanti Armelinda; Frischa Faradilla Arwinda Mongan; Maria Yessica Halik (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2022)
This studi aims to analize the application of systems andprocedues for drug procurement at the Matakali Public HealthCenter in Polewali Regency. The type of research used is a type ofqualitative research. Informacnts in this study were selected bypurposive sampling and data were collected through in-depthinterviews and observation. The results of the study indicate that theplanning system and accounting procedures that have beenimplemented have not been fully effective and efficient, this can beseen from the recordings that have not been computerizwd in realtime. Information on drug availability that cannot be obtained in realtime.